(untitled) - Nassar, David S. (New York, 1999)
This book takes you to the leading edge of today's electronic trading technology. Regardless of the prevailing market sentimentbull, bear, or sidewaysits techniques and strategies will help you take advantage of the profit opportunities that occur every trading day.
Keywords: Electronic trading of securities,Day tradinding,An toàn thương mại điện tử,Thời đại thương mại